RETRACTED: Search query as a methodological indicator of new pedagogical conceptualizations (on the example of hip-pedagogy) - Pankin Arkadiy; Fedotova Olga; Latun Vladimir (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001